Sarcoidosis presenting as vocal cord palsy: an unusual presentation and literature review - Raja, Mohummad Hassan Raza (Respirol Case Rep, 2020)
We report the case of a 60‐year‐old woman, presenting with left vocal cord paralysis (VCP). Diagnostic evaluation revealed sarcoidosis to be the underlying pathology. Computed tomography (CT) scans exhibited enlarged subcarinal, pretracheal, and prevascular lymph nodes as the possible mechanism of left VCP through compression of the left recurrent laryngeal nerve. Initial treatment with oral prednisolone and azathioprine led to remission of symptoms; however, tapering of dosage led to relapse of cough without any signs of VCP. The dosage of prednisolone was further boosted, leading to complete remission. A review of literature reveals 20 cases have been reported to date, with all but one involving the left vocal cord. This is the first reported case, with a relapse of the disease without a relapse of VCP, indicating the rarity of sarcoidosis‐associated VCP.